Serum uric acid and high-sensitivity C-reactive protein levels among people living with HIV on dolutegravir and ritonavir-boosted atazanavir-based antiretroviral therapy: a comparative cross-sectional study - Waritu, Nuredin Chura; Nair, Suresh Kumar P.; Usure, Rashed Edris; Jemal, Mohammed (Frontiers in Medicine, 2024)
Background After the introduction of antiretroviral therapy, the care given to people living with HIV has become complicated by the appearance of comorbidities as a result of HIV and HAART toxicities, in which cardiovascular disease got the most attention. So, this study aimed to assess serum uric acid and high-sensitivity C-reactive protein levels among people living with HIV on dolutegravir (DTG) and ritonavir-boosted atazanavir (ATV/r)-based therapy. Methods An institutional-based comparative cross-sectional study was conducted from November 4, 2021, to January 4, 2022. An equal number of dolutegravir- and ritonavir-boosted atazanavir-treated patients (n = 86 each) were enrolled. A consecutive sampling method was used to select participants. Data were entered into Epidata version 4.6, exported to SPSS version 25.0, and analyzed using Chi-square, Student’s t-test, Mann–Whitney U-test, and logistic regression. Statistical significance was set at p < 0.05. Results The prevalence of hyperuricemia and high-sensitivity C-reactive protein levels ≥2 mg/L were 46.5% (40/86) and 24.4% (21/86) in the DTG group, and 30.2% (26/86) and 44.2 (38/86) in the ATV/r group, respectively. When compared to ATV/r, a higher mean level of uric acid was found among DTG-based regimens (5.38 mg/dL). Duration of ART (AOR = 2, 95% CI: 1.2, 4.4) and DTG-based regimen (AOR = 1.9, 95% CI: 1.04, 3.8) were significant predictors of developing hyperuricemia. ATV/r-based regimen (AOR = 3, 95% CI: 1.5, 8.3) and high waist circumference (AOR = 2.5, 95% CI: 1, 3.5) were significantly associated with increased high-sensitivity C-reactive protein levels. Conclusion It is observed that DTG-based and ATV/r-based ART are associated with hyperuricemia and increased high-sensitivity C-reactive protein levels, respectively. Therefore, it is important to consider and evaluate serum uric acid and high-sensitivity C-reactive protein levels in patients taking DTG and ATV/r-based ART, as well as among those on HAART for years and with a higher waist circumference, so as to detect and prevent early the risk of having CVD.